2014
DOI: 10.3329/jbau.v11i1.18220
|View full text |Cite
|
Sign up to set email alerts
|

Environmental health hazard of arsenic on epididymis and ductus deferens in male Black Bengal Goats

Abstract: Histomorphological changes of epididymis and ductus deferens in male Black Bengal goat due to arsenic were studied. A total of 12 male Black Bengal goats, in which 6 were collected from arsenic affected areas of Mymensingh district and another 6 were collected from hill tracts of Chittagong which were arsenic free.The goats were sacrificed by piercing carotid artery and the samples (Epididymis and Ductus deferens) were collected immediately. Samples were prepared and stained with haematoxylin and eosin stain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The mass of testes is an important index of reproductive toxicants (Aman, ), and reduction in mass of testes may be due to elimination of germ cells (Chapin & Lamb, ). However, no significant difference was reported in the mean values of weight, length, width and breadth of both testes as well the epididymis and ductus deferens in naturally arsenic‐affected goats (Wares, Awal, Nasrin, & Siddiqi, ; Wares et al., ). This difference might be due to relatively low doses of arsenic during natural exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The mass of testes is an important index of reproductive toxicants (Aman, ), and reduction in mass of testes may be due to elimination of germ cells (Chapin & Lamb, ). However, no significant difference was reported in the mean values of weight, length, width and breadth of both testes as well the epididymis and ductus deferens in naturally arsenic‐affected goats (Wares, Awal, Nasrin, & Siddiqi, ; Wares et al., ). This difference might be due to relatively low doses of arsenic during natural exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In goats, it has been found that consuming water contaminated with arsenic can cause damage to the body and the physiological condition [ 12 ], because exposure to arsenic results in its deposition in different body tissues such as the heart, muscles, kidneys and liver of animals, which produces different toxic effects in these tissues [ 13 ]. On the other hand, there are reports that arsenic also causes damage at the reproductive level; in fact, damage has been found in the epididymis and vas deferens [ 14 ], as well as in sperm quality [ 11 , 15 , 16 ]. These alterations caused by the high levels of arsenic in the animal’s organism can be attributed to the oxidative stress it exerts, as it can damage DNA, leading to a cascade of events, some of which can be adverse.…”
Section: Introductionmentioning
confidence: 99%